Consolidation of family institution through the comprehension of marriage philosophy in Islam - Nizaita, Omar; Zanirah, Wahab; Rahimah, Embong; Razi, Yaakob (Serials Publications, 2017)
Every living creature possesses a desire to have a spouse. The attraction between two different sexes is a fundamental base of preserving and expanding a species’s existence. This desire to pair up among human beings leads to a unique system of marriage. Marriage is a knot tied between a male and a female through certain procedures to connect not only their bodies, but also their souls to create a happy and serene sharing life. However, it is worrying that the rate of divorce in Malaysia seems to be increasing time by time. Reportedly, there is one divorce happening every 15 minutes. Most of the cases involve young couples of 31 to 35 years old. In a research done by the Department of Islamic Affairs of Malaysia in 2007, it was proven that 59.9 percentage of the divorce cases involved marriages aged under ten years. With regard to this phenomenon, the high value of Islamic civilization, which was revealed by Allah to the prophets, is studied and examined. It is evinced that Islam exhibits an outstanding philosophy of marriage to be learned and lived by both husbands and wives in order to create an excellent family institution. Throughout this research as a qualitative approach, Koran and hadeeth, which are two main sources in the teachings of Islam, as well as Seerah Nabawiyah (the prophet’s biography), are studied and analysed to comprehend deeply the concept, purpose, principles, values and virtues of marriage in Islam. This research is hoped to make a contribution in improving and building resiliency to the family institution which is said to be frail these days.